2005
DOI: 10.1007/bf03167052
|View full text |Cite
|
Sign up to set email alerts
|

Contenido de vitamina A en dieta de cafetería y expresion de receptores nucleares en tejido adiposo de rata

Abstract: The aim of this study was to determine the effects of cafeteria diet containing control or elevated level of vitamin A on the expression of nuclear receptors in adipose tissue. Male Wistar rats were submitted to 3 experimental diets during 8 weeks, a standard diet and two hyper-energetic, hyperlipidic "cafeteria" diets containing normal (Caf) or higher (Caf+) vitamin A level. During the experiment, body weights and energy intakes were measured. At the end of the experimental period, subcutaneous adipose tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…For this purpose, the aim of the present study was to determine the mechanisms through which EPA ethyl ester improves lipid metabolism in an experimental animal model of obesity induced by high-fat (cafeteria) diet. As previously reported by our group and others [4,27,36,37], this is an accepted model of diet-induced obesity that shares common features with Western diet and drives towards metabolic syndrome conditions. The dose of EPA ethyl ester used in the present study has been previously reported to have beneficial metabolic actions in rodents.…”
Section: Discussionsupporting
confidence: 52%
“…For this purpose, the aim of the present study was to determine the mechanisms through which EPA ethyl ester improves lipid metabolism in an experimental animal model of obesity induced by high-fat (cafeteria) diet. As previously reported by our group and others [4,27,36,37], this is an accepted model of diet-induced obesity that shares common features with Western diet and drives towards metabolic syndrome conditions. The dose of EPA ethyl ester used in the present study has been previously reported to have beneficial metabolic actions in rodents.…”
Section: Discussionsupporting
confidence: 52%
“…WAT is able to store as much as 20% of the whole body reserve of vitamin A, under retinol ester forms. After its incorporation into WAT, retinyl esters could be transformed into retinoic acid and act on adipose tissue gene expression [4,50], suggesting that WAT possesses all the equipment necessary for vitamin A metabolism (see Table 1), as it has been previously demonstrated for HSCs. This signaling pathway in WAT suggests that vitamin A could directly affect the regulation of energy balance by the control of the fat mass [10,66].…”
Section: Adipocyte Physiology and Metabolismmentioning
confidence: 82%
“…Whereas PPARγ is expressed in small amounts in preadipocytes, its synthesis increased during the process of adipogenesis (9). Furthermore, it is well known that retinoids could be involved in the control of adiposity through the activation of retinoid acid receptors (RARs) and retinoid X receptors (RXRs) (2,20), being RARγ and RXRα specifical isoforms of WAT (2,30). Besides, these nuclear receptors had a close relationship with PPARγ: whereas the RARγ/RXRα heterodimer formation leads to recruitment of adipogenesis co-repressors, the creation of coactivators are related with PPARγ/RXRα heterodimer development, which is ultimately translated into an alteration of the activity of the gene from repressed to activated (5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous to the RT-PCR determination, the RNA quality was estimated by the bioanalyzer Agilent 2100, using the kit RNA 6000 Nano assay (Agilent technologies). All procedures were performed as described by REDONNET et al (31) and BAIRRAS et al (2). β2-microglobulin was used as housekeeping gene.…”
Section: Gene Expression Analysis (Northern Blot and Quantitative Reamentioning
confidence: 99%